LAW ENFORCEMENT BPOM BANDA ACEH AGAINST CRIMINAL ACTS. FOOD PRODUCTION USES BORAX AND FORMALIN - Yuhermansyah, Edi; Akbar, Hajarul; Alya, Cut (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
The need for food production is inseparable from the efforts of consumers who want food to last longer, thus triggering food producers to compete to make the food according to the wishes of consumers in a way that is not justified by laws and regulations, but this method will cause various diseases, even death. BPOM has a basis for law enforcement against criminal acts of food production according to the provisions of Article 6 Paragraph (1) and Article 7 Paragraph (2) of Law Number 8 of 1981 concerning criminal procedural law. The questions in this thesis are how is the law enforcement of food production crimes carried out by BPOM Banda Aceh, and what are the inhibiting and supporting factors for food production crimes. This study uses field research and uses qualitative research methods with an empirical juridical approach and applies two forms of data collection methods, namely interviews and documents. The results of the study showed that law enforcement was carried out by BPOM Banda Aceh, namely based on evidence from testing results, the process was submitting evidence to the prosecutor's office, destroying evidence, imposing administrative sanctions, BPOM obstacle factor was the lack of investigators, investigators did not have much authority in detention, requests from consumers, food producers do it repeatedly, while the supporting factors for BPOM investigators are having a laboratory car, cooperative actors. From the explanation above, the authors can conclude that law enforcement by BPOM investigators is still not optimal and still has obstacles.